BOOK REVIEW: Ulrike Krampl, “Les secrets des faux sorciers. Police, magie et escroquerie à Paris au XVIIIe”, Paris: Éditions de l’EHESS, 2011 - EPPEL, Marius (Studia Universitatis Babeș-Bolyai Historia, 2019)
The book of Ulrike Krampl draws the readers’ attention to a subject that is too little investigated by today’s historians. French historiography is famous throughout the world also for its historiographic productions that discuss subjects like magic and sorcery. The majority of the French historians and anthropologists who are specialists in researching the phenomenon of magic asserted themselves especially between 1970 and 1980, and they focused particularly on the 17th century. With regard to the evolution of magic belief in Paris during the Age of Enlightenment – when it became obsolete, because it did not represent a “social custom” anymore, being replaced with alchemy – there are just a few research works as detailed as that of Ulrike Krampl. Given the fact that this paper represents her doctoral thesis, the researcher at the École des Hautes Études en Sciences Sociales was granted the necessary time for studying and analyzing with remarkable accuracy the documents at Bibliothèque de l'Arsenal, the Archives de la Bastille Fund, the National Library of France, Manuscrits Occidentaux Department, National Archives, the Parlement de Paris, Affaires criminelles, and the Papiers des commissaires du Châtelet Funds as well as a multitude of documentary editions, papers, studies, and articles.